13C and 15N NMR spectra of high‐energy polyazidocyanopyridines. (11th August 2016) - Chapyshev, Sergei V.; Chernyak, Alexander V.; Ushakov, Evgeny N.
Abstract: 13 C and 15 N NMR spectra of high‐energy 2, 4, 6‐triazidopyridine‐3, 5‐dicarbonitrile, 2, 3, 5, 6‐tetraazidopyridine‐4‐carbonitrile and 3, 4, 5, 6‐tetraazidopyridine‐2‐carbonitrile are reported. The assignment of signals in the spectra was performed on the basis of density functional theory calculations. The molecular geometries were optimized using the M06‐2X functional with the 6‐311+G(d, p) basis set. The magnetic shielding tensors were calculated by the gauge‐independent atomic orbital method with the Tao–Perdew–Staroverov–Scuseria hybrid functional known as TPSSh. In all the calculations, a polarizable continuum model was used to simulate solvent effects. This approach provided accurate predictions of the 13 C and 15 N chemical shifts for all the three compounds despite complications arising due to non‐coplanar arrangement of the azido groups in the molecules. It was found that the 15 N chemical shifts of the Nα atoms in the azido groups of 2, 4, 6‐triazidopyridines correlate with the 13 C chemical shifts of the carbon atoms attached to these azido groups. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Complete assignment of all signals in the 13 C and 15 N NMR spectra of three high‐energy polyazidocyanopyridines is reported.